Exploring strategy text and cases - Whittington, Richard 1958-; Angwin, Duncan 1953-; Regnér, Patrick; Johnson, Gerry; Scholes, Kevan (Pearson, 2023)
"Exploring Strategy is an essential introduction to the field, designed to help you think and behave like a manager. From entrepreneurial start-ups to multinationals and charities to public sector organisations, this book tackles the big questions – how organisations prosper, grow, innovate, and change. This latest Text and Cases edition provides a wealth of extra case studies written by experts to aid and enrich your understanding. Examples include Siemens, Mars, Formula 1, Glastonbury, and the Indian Premier League." --pearson.com
Keywords: Business planning; Strategic planning; Business planning / Case studies; Strategic planning / Case studies